2008
DOI: 10.1080/03004430600722671
|View full text |Cite
|
Sign up to set email alerts
|

Chinese and American preschool teachers’ beliefs about early childhood curriculum

Abstract: This study examined the consistency of Chinese preschool teachers' curriculum beliefs and selfreported practices, similarities and differences between American and Chinese teachers' beliefs, and associations between teachers' personal, professional and socio-cultural characteristics and curriculum beliefs. A total of 296 Chinese teachers and 146 American teachers completed the Teacher Beliefs Scale and the Teachers' Background Information Questionnaire. Chinese teachers also completed the Instructional Activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 22 publications
12
69
0
8
Order By: Relevance
“…If one uses majors or degrees as rough approximations, it seems as if preschool teachers with higher education levels or with specialized early childhood training agreed more strongly with appropriate teaching and learning beliefs (McMullen 1998;Wang et al 2008). It is important though to broaden this insufficient state of research by examining the relation of specific educational characteristics to prospective preschool teachers' beliefs.…”
Section: Educational Determinantsmentioning
confidence: 99%
“…If one uses majors or degrees as rough approximations, it seems as if preschool teachers with higher education levels or with specialized early childhood training agreed more strongly with appropriate teaching and learning beliefs (McMullen 1998;Wang et al 2008). It is important though to broaden this insufficient state of research by examining the relation of specific educational characteristics to prospective preschool teachers' beliefs.…”
Section: Educational Determinantsmentioning
confidence: 99%
“…Teachers have their thought processes in their mind gained through their own personal practical experiences which may differ from those in curriculum principles and concepts taught in education and child development courses (Ableser, 2003;Spodek & Saracho, 1999;Wen, Elicker, & McMullen, 2011 (Howe, Jacobs, Vukelich, & Recchia, 2012;Hyson, 2003;Hyun & 2001;Rice, 2003). In addition, studies carried by Dedeoğlu and nlat (2012) in Turkey, Nganga (2009) in Kenya, Ejuu (2012) in Uganda, Kweka et al (2000) and Mtahabwa (2007) in Tanzania, Li et al (2011) in China, Wood (2004 in England, Tayler (1991) in Australia, William and Charles (2008) in Caribbean, Wang et al (2008) in China and America, recommended that concerned…”
Section: Ecec Curriculum Enactment In a Global Perspectivementioning
confidence: 99%
“…Wang et al [18] found that government regulation was a top factor considered by Chinese teachers to influence their teaching practice. The official preschool curriculum has complex effects on teachers' practice of play.…”
Section: Teachers' Practice Of Play In Chinese Preschoolsmentioning
confidence: 99%
“…In the level of early childhood education, the basic themes of the curriculum reform are catering to individual development, focusing on all-around development, and emphasizing appropriate development at appropriate stages [11,18].Play, which is "at the heart of developmentally appropriate early childhood programs", and "should be at the center of every curriculum" [19], is highlighted in Chinese preschool curriculum reform.…”
Section: Dichotomy Of Play and Learning Reflected In Different Reformmentioning
confidence: 99%